A Short Review on the Efficacy of Derivatives of Curcumin - Sameera, Rege; Varshneya, Megha; Momin, Shamim (Current Nutraceuticals, 2022)
Curcumin with medicinal value should possess good bioavailability and stability. Unfortunately, the bioavailability of curcumin is less, and its stability depends on the medium. After intake of curcumin, it undergoes metabolism to form metabolites, which are bioactive and show better bioavailability than curcumin. Hence, the disadvantages of curcumin can be overcome by the formation of its synthetic derivative. In this review paper, the derivatives of curcumin, namely tetrahydrocurcumin, hexahydrocurcumin, octahydrocurcumin, deketene curcumin, and dimethoxycurcumin are discussed. The diketo group, diene moiety, and ortho-methoxy phenolic groups present in curcumin influence its properties. Curcumin undergoes degradation in alkaline and non-polar mediums, mainly because of its property to exhibit keto-enol tautomerism, which is further enhanced due to the presence of diene moiety and ortho-methoxy phenolic groups. If the keto-enol tautomerism is inhibited by its derivatization, then its stability is improved. This is especially true in the case of hexahydrocurcumin, octahydrocurcumin, and deketene curcumin, which do not possess an active methylene group. Although tetrahydrocurcumin undergoes keto-enol tautomerism, the degradation of enol tautomer is prevented due to the absence of diene moiety. The activities of curcumin are medium dependent, whereas the activities of hydrogenated derivatives of curcumin and deketene curcumin are medium independent. Dimethoxycurcumin exhibits keto-enol tautomerism and can undergo degradation in alkaline and non-polar mediums at a faster rate than curcumin. The reason is that the strong activating hydroxyl groups in curcumin are replaced by a stronger activating methoxy group in dimethoxycurcumin. On the other hand, in acidic and polar mediums, the rate of beneficial activities of dimethoxycurcumin is more than curcumin. Also, the bioavailability of the above-mentioned derivatives of curcumin is more than curcumin.
Keywords: deketene curcumin